Service Quality Analysis on the Satisfaction of Umrah School Participants at the Rihaal Umrah and Education Bureau - Yuliar, Ade; Handayani, Sri (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
This study aims to determine the effect of service quality on customer satisfaction at Rihaal Umrah and Education Bureau. This study uses a type of quantitative research using simple linear regression analysis. The independent variable in this study is service quality, and the dependent variable in this study is customer satisfaction. The population in this study was gained the Umrah participants of the 2019 period, with a sample of 36 respondents. The results of this study showed that the service quality variable has a significant effect on customer satisfaction. It means that if the quality of service increases, the customer satisfaction of umrah’s school will also increase